Quality Evaluation of Metabolic-Associated Fatty Liver Disease Guidelines and Expert Consensus - Chen, Meijing; Chen, Ying; Liu, Dun; Li, Ka; Hu, Rong; Chen, Jingyi; Jiang, Xiaoying; Lin, Jinqing (Hormone and Metabolic Research, 2024)
The purpose of this study is to evaluate and analyze the quality of guidelines and expert consensus on clinical practice regarding metabolically associated fatty liver disease (MAFLD) over the past five years. Data from the websites were retrieved using computers. We evaluated guidelines and expert consensus on MAFLD that were officially published between January 1, 2018 and March 24, 2023. Two evaluators independently examined the literature and extracted data. The included literature on guidelines and expert consensus was then subjected to quality review and analysis using assessment tools from Appraisal of Guidelines for Research and Evaluation (AGREE) II and the Joanna Briggs Institute Qualitative Assessment and Review Instrument (JBI-QARI) (2016). The intraclass correlation coefficient (ICC) values of all items on the AGREE II scale for the two evaluators were greater than 0.75, indicating a high degree of agreement between their assessments. Scope and purpose (48.90%), participants (49.21%), rigor in the formulation process (56.97%), clarity of expression (90.08%), applicability (66.08%), and independence of file compiling (60.12%) were the AGREE II scoring items with the standardized average scores. Apart from the participants, the average scores of all the scoring items in the guidelines from other countries other than China were higher than those from China (|Z|+>+2.272, p+<+0.05). MAFLD guidelines must be revised to enhance their methodological quality. When creating guidelines, it is recommended that the formulators strictly adhere to the formulation and drafting standards of AGREE II and elevate the quality of the guidelines.
Keywords: expert consensus; guidelines; metabolically associated fatty liver disease (MAFLD); non-alcoholic fatty liver disease (NAFLD); quality evaluation